Can Emotional Competence Be Taught in Higher Education? A Randomized Experimental Study of an Emotional Intelligence Training Program Using a Multimethodological Approach - Gilar-Corbí, Raquel; Pozo-Rico, Teresa; Sánchez, Barbara; Castejón, Juan Luis (Frontiers in Psychology, 2018)
Since the introduction of the Bologna Process, the goal of education has been not only to acquire technical skills but also to master other skills, such as teamwork, effective communication skills, time optimization, and the ability to manage one's emotions. The present work describes a program to develop emotional intelligence in higher education, the “Emotional Intelligence Training Program”, with a multimethodological approach that offers the opportunity for university students to develop their emotional intelligence. A total of 192 higher education students participated in this educational experience. Of the participants, 66% were women, and 34% were men; the average age of the sample was 18.83 years with a standard deviation of 2.73. The results indicate that our program can help improve emotional intelligence through three proposed methodologies: online, in the classroom, and coaching. It has been demonstrated that the program is effective in the three methodological modalities presented, offering a range of possibilities to future users because it is possible to select the most appropriate modality based on the resources and possibilities available in each situation. Finally, Future research should focus on the application of this program to assess the acquisition of emotional competences at the postgraduate level.